PENGEMBANGAN PARIWISATA BERBASIS MODAL SOSIAL DAN STORYTELLING: STUDI KASUS PROGRAM SELASA WAGEN DI MALIOBORO, YOGYAKARTA - Masriah, Imas; Suheryadi, Heru; Toro, Sahlan; Suryantari, Yulita (Jurnal Sains Terapan Pariwisata, 2025)
Purpose: This study aims to analyze the integration of social capital and storytelling in the Selasa Wagen program in Malioboro, Yogyakarta, focusing on its role in cultural preservation, local economic development, and sustainable tourism management. Research Methods: A qualitative case study approach was employed. Data were collected through semi-structured interviews with 15 informants (government officials, street vendors, community leaders, and tourists), participatory observation, and document review. Data were analyzed thematically using NVivo. Implication: Findings indicate that Selasa Wagen integrates social trust, networks, and norms with cultural narratives, creating an inclusive tourism model. This model not only preserves heritage but also strengthens local identity, enhances visitor experiences, and fosters collaborative governance.